Diversify your fund portfolio (John Wiley & Sons, Inc., 2005)
The Morningstar Investment Coach: Building a Diversified Portfolio allows readers to take the next step in their mutual fund journey. With discussions of topics such as gauging risk and return together, how to choose index and international funds, and the importance of knowing your mutual fund manager, this practical guide will help readers sharpen their mutual fund investing skills.